UJI PENDAHULUAN PENGARUH EKSTRAK AIR DARI TUMBUHAN TERHADAP KETERJADIAN KARAT PADA CAKRAM DAUN KOPI DI LABORATORIUM - Ginting, Cipta; Mujim, Subdi; Evizal, Rusdi (Universitas Lampung, 2004)
Preliminary test on the effect of water extract from plants on rust incidence on coffee leaf disks at the latroratory. The objective of this study was to determine the influence of several water extract from plants on rust incidence on coffee leaf disk a laboratory condition. The study was done from March to June 2003. Treatments were arranged in a randomized complete block design with four replications, One experimental unit consisted of eight leaf disks with 2 cm in diameter. To prepare water extract, 1 00 g of plant or its part was homogenized with 100 ml sterilized distilled water. After being passed through four layers of sterilized cheesecloth, the mixture was defined as the aliquot. Ten percent of the aliquot was sparyed on leaf disks before inoculation. As inoculum, uredospores developed on leaves under field condition were taken with sterilized scalpel and placed in sterilized distilled water and counted with hemacyometer to get suspension (4x105 uredospores per ml) spores per ml). Data on disease incidence were analyzed with ANOVA and Duncan test. The results showed that disease incidence was significantly reduced by water extract processed from the leaves of Piper betle, Azadirachta indica, and Eugeni aromatica, the rhizomes of Zingiber afficinale and Curcumq longa, stem of Cymbopogon citratus, Allium ascalonium, A.sativa, and copper fungicide. Disease was not significantly reduced in leaf disks sprayed with extract prepares from the leaves of Piper retrofractum, P. nigrum, the rhizomes of Imperata cylindrica and Alpina galanga, A. cepa,Ageratum comysoides, and Elephantopus scaber.